Effect of Social Support on Psychological Distress and Disease Activity in Inflammatory Bowel Disease Patients. Issue 7 (20th April 2018) - Slonim-Nevo, Vered; Sarid, Orly; Friger, Michael; Schwartz, Doron; Sergienko, Ruslan; Pereg, Avihu; Vardi, Hillel; Singer, Terri; Chernin, Elena; Greenberg, Dan; Odes, Shmuel; ,
Abstract: Background: Psychological distress increases morbidity in ulcerative colitis (UC) and Crohn's disease (CD). We examined whether social support is associated with distress and disease activity. Methods: There were 110 UC and 147 CD patients who completed sociodemography, economic status, disease activity (UC: Patient Simple Clinical Colitis Activity Index (P-SCCAI), CD: Patient Harvey-Bradshaw Index . (P-HBI), Multidimensional Scale of Perceived Social Support (MSPSS), Brief Symptom Inventory with Global Severity Index (GSI) of psychological distress, and 2 health-related quality-of-life scales (SF-36 Physical Health and Mental Health, and Short Inflammatory Bowel Disease Questionnaire (SIBDQ). Analysis included multiple linear regressions and structural equation modeling. Results: Disease activity was mild: UC: P-SCCAI 2.9 ± 3.5, CD: P-HBI 4.7 ± 4.7. Physical Health was better in UC 46.6 ± 11.4 versus CD 43.7 ± 10.9 ( P < .02). GSI was lower in UC 0.6 ± 0.7 than CD 0.8 ± 0.7 ( P = .002). MSPSS total score was equal in UC (5.9 ± 1.2) and CD (5.9 ± 1.1). MSPSS total correlated with P-SCCAI (correlation coefficient ‒0.240), GSI in UC (‒0.470), and GSI in CD (‒0.333). Economic status correlated with GSI in UC (‒0.408) and CD (‒0.356). MSPSS predicted GSI, Mental Health, and SIBDQ in UC and CD, and predicted P-SCCAI but not P-HBI; economic status predicted all the foregoing. Path analysis depicted GSI as mediating the effects of MSPSS and economic status on disease activity in both UC and CD. MSPSS (UC: β ‒0.34, CD: β ‒0.37) and economic status (UC: β ‒0.38, CD: β ‒0.22) reduced GSI, which then increased the disease activity (UC: β 0.56, CD: β 0.42). Conclusions: Social support and economic status are linked to UC and CD patients' well-being. Interventions addressing these issues should be part of management.